DIGITAL CREATIVE ECONOMY WORKSHOP: BUILDING CAREERS AND MONETIZATION IN THE DIGITAL ERA - Afif Naufal, Hanif; Lastuti, Yeti; Wiralaga, Harya Kuncara; Iranto, Dicky; Maulida, Ervina (Faculty of Economics and Business, Universitas Negeri Jakarta, 2025)
This study presents the outcomes of the Digital Creative Economy Workshop, designed to equip senior high school Economics teachers in Jakarta with essential skills for navigating the digital economy. Held on June 18, 2025, the workshop trained 45 teachers from 10 schools on digital literacy, AI-based learning tools, and digital monetization strategies. Using a structured approach of training and evaluation, participants engaged with platforms like Eduaide and Magic School. Pre- and post-test results showed marked improvements across all learning areas: understanding of the digital creative economy rose from 3.2 to 4.4, AI tool utilization from 3.1 to 4.3, and digital monetization knowledge from 3.0 to 4.1. The workshop successfully enhanced teachers’ readiness to integrate digital technologies in Economics education, supporting Sustainable Development Goal 4 (Quality Education). Continued professional development and infrastructure support are recommended to sustain these advancements